Collective bargaining and innovation in Germany * a case of cooperative industrial relations? - Addison, John T.; Teixeira, Paulino; Bellmann, Lutz; Evers, Katalin (Industrial relations, 2017)
At the level of theory, the effect of collective bargaining on innovation is contested. The large proponderance of the U.S. evidence clearly points to adverse effects, but other‐country experience suggests that certain industrial‐relations systems, or the wider regulatory apparatus, might even tip the balance in favor of unions. Our pooled cross‐ section and difference‐in‐differences estimates provide some weak evidence that German collective bargaining inhibits innovation. However, in conjunction with workplace representation, there is the suggestion that it might actually foster innovative activit